Repeated Whole-Body Exposure to Low-Dose Radiation Combined With Topical Application of Basic Fibroblast Growth Factor and Zinc Accelerates Wound Healing in Diabetic Rats - Hai-feng Zhang; Jie Cheng; You Lv; Feng-sheng Li; Guang-yu He; Brain Wang; Lu Cai; Wei-ying Guo (SAGE Publishing, 2018)
We reported the acceleration of skin wound healing in diabetic rats by repeated exposure to low-dose radiation (LDR). Here, we explored whether the wound healing could be further improved when LDR was combined with a topical application of basic fibroblast growth factor (bFGF) or zinc. Wounds were established on the backs of type 1 diabetic rats induced by a single injection of streptozotocin. Rats were treated daily with normal saline (Diabetes), LDR, bFGF, zinc, or combined 3 treatments for 5 consecutive days with a 2-day break between each consecutive 5-day treatment. Changes in wound size, histopathology, and microvessel density were assessed on days 5, 10, and 15, respectively, once treatment is started. All treatment regimens significantly accelerated skin wound healing, tissue remodeling, and new vessel formation compared to diabetes group. However, the combined LDR plus bFGF and zinc provided a better beneficial effect on wound healing than either one of these treatments alone. Further, we found that the effects of LDR and bFGF were similar, whereas zinc alone induced a weaker response. Our results suggest that whole-body LDR plus the topical application of bFGF and zinc can further accelerate wound healing in diabetic rats.